2016
DOI: 10.1371/journal.pone.0163653
|View full text |Cite
|
Sign up to set email alerts
|

Social and Cultural Factors Affecting Maternal Health in Rural Gambia: An Exploratory Qualitative Study

Abstract: BackgroundThe high rate of maternal mortality reported in The Gambia is influenced by many factors, such as difficulties in accessing quality healthcare and facilities. In addition, socio-cultural practices in rural areas may limit the resources available to pregnant women, resulting in adverse health consequences. The aim of this study is to depict the gender dynamics in a rural Gambian context by exploring the social and cultural factors affecting maternal health.Methods and FindingsFive focus group discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 46 publications
9
75
0
1
Order By: Relevance
“…The above findings were supported by those of some previous studies carried out in Gambia (Lowe et al. ) and Nepal (Simkhada et al. ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The above findings were supported by those of some previous studies carried out in Gambia (Lowe et al. ) and Nepal (Simkhada et al. ).…”
Section: Discussionsupporting
confidence: 90%
“…These results indicated that heavy household workloads were a major issue for most of the pregnant women who were not able to manage their time to utilize prenatal care (Lowe et al. ; Simkhada et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Speizer et al (2014) highlighted the role of community norms in institutional delivery but stated that women autonomy played a major role in ensuring these deliveries are facility based. This was also the case in Ethiopia as found by Tiruneh et al (2017) Findings on the relationship between women autonomy and maternal healthcare utilisation is explained by the fact that younger women in marriages are not as educated as older women, don't have the financial wherewithal to make decisions that have financial implications and follow through, don't have adequate information to ensure evidence-based decision making and also perceive that they are inexperienced to make decisions on issues related to motherhood and pregnancy, hence the dependence of their mother in-laws but this is in contrast to the findings of Hagos et al (2014) in Ethiopia and Lowe et al (2016) in Gambia where it was found that women who had autonomy in decision making about place of delivery were less likely to deliver in a health facility and that at the time of delivery, the decision to receive care by trained personnel was often beyond the women's control, resulting in birth-related complications respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Another study showed that most of these young women due to their uniqueness (Banke- Thomas et al, 2017), neither benefited from these services nor derive any joy of motherhood, as a result of their young age, lack of autonomy and inexperience (Baral et al, 2010). Studies have examined the relationship between women's autonomy and utilisation of any or all of the maternal health care services, and have found association between them (Asweto et al, 2014;Baral et al, 2010;Bhandari et al, 2017;Hagos et al, 2014;Lowe et al, 2016;Speizer et al, 2014;Thapa, 2012;Tiruneh et al, 2017). Other factors such as age, education, employment or labour force participation and wealth quintile have also been found to be associated with maternal healthcare utilisation (Acharya et al, 2017;Adhikari, 2016;Asweto et al, 2014;Banke-Thomas et al, 2017;Baral et al, 2010;Dahiru and Oche, 2015;Deo et al, 2015;Fawole and Adeoye, 2015;Kamiya, 2010;Okeshola and Sadiq, 2013;Sebayang et al, 2017;Sharma et al, 2007;Situ, 2013;Tarekegn et al, 2014;Teklehaymanot et al, 2017;Tiruneh et al, 2017;Urbaeva, 2015;Woldemicael, 2007aWoldemicael, , 2007bWorkineh and Hailu, 2014;Yaya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have focused on explaining how social factors like low income, occupation, heavy work during pregnancy and education influence the mother during pregnancy . Studies have revealed that populations with greater inequities have a greater proportion of newborns with LBW .…”
Section: Discussionmentioning
confidence: 99%